Application of perturbation idea to well-known Hencky problem: A perturbation solution without small-rotation-angle assumption. (July 2017) - Lian, Yong-sheng; He, Xiao-ting; Liu, Guang-hui; Sun, Jun-yi; Zheng, Zhou-lian
Highlights: The Hencky membrane equation giving up small-rotation-angle assumption is established. This problem may be regarded as a perturbed system for the problem with small-rotation-angle assumption. The load is selected as a perturbation parameter. The perturbation idea is applied to the solution for the problem. The decomposed equations of all levels are still solved by using series expansion. Abstract: In existing studies, the well-known Hencky problem, i.e. the large deflection problem of axisymmetric deformation of a circular membrane subjected to uniformly distributed loads, has been analyzed generally on small-rotation-angle assumption and solved by using the common power series method. In fact, the problem studied and the method adopted may be effectively expanded to meet the needs of larger deformation. In this study, the classical Hencky problem was extended to the problem without small-rotation-angle assumption and resolved by using the perturbation idea combining with power series method. First, the governing differential equations used for the solution of stress and deflection in the perturbed system were established. Taking the load as a perturbation parameter, the stress and deflection were expanded with respect to the parameter. By substituting the expansions into the governing equations and corresponding boundary conditions, the perturbation solution of all levels were obtained, in which the zero-order perturbation solution exactly corresponds to the small-rotation-angle solution, i.e. the solution of the unperturbed system. The results indicate that if the perturbed and unperturbed systems as well as the corresponding differential equations may be distinguished, the perturbation method proposed in this study can be extended to solve other nonlinear differential equations, as long as the differential equation of unperturbed system may be obtained by letting a certain parameter be zero in the corresponding equation of perturbed system.